Total Hip Arthroplasty after Treatment of Pseudojoint Infection in a Patient with a Highly Dislocated Hip. (25th June 2013) - Park, Kyung-Soon; Seon, Jong-Keun; Nah, Seon-Yoon; Yoon, Taek-Rim
Abstract : Infection at the pseudoacetabulum in a patient with a high hip dislocation has not been reported previously in the English literature. We report a case of total hip arthroplasty in a 28-year-old female who presented to us with hip pain following debridement of the infected pseudojoint in a case of neglected developmental dysplasia of the hip. The infection was treated with thorough debridement and drainage. However, even after achieving complete infection control, this patient complained of disabling right hip joint pain. Total hip arthroplasty with subtrochanteric osteotomy was performed to relieve the pain and improve gait. After surgery, the patient's symptoms were relieved. We consider that in this case of acute pseudojoint infection simple arthrotomy and debridement combined with irrigation and drainage provide effective treatment. But muscle weakness and more increased joint laxity can cause hip pain even after infection control. So total hip arthroplasty is likely to be necessary after the infection has been controlled in a patient with a highly dislocated hip.